The Reflections on Governance and the Rule of Law in Zimbabwe: Political Philosophy of Nicollo Machiaevelli - J. Moyounotsva Marava (Research Developments in Arts and Social Studies Vol. 5, 2022)
Governance and the rule of law have become a topical agenda in the academia and international conferences, where the issue of human rights violation has been widely discussed, both formally and informally. Media is dominated by political discourse centered on governance, leadership crisis economic crisis, ideal political leadership and legitimacy. Machiavellian philosophy has been employed as a benchmark to analyse the Zimbabwean situation. The colonisation of Zimbabwe and other African countries resulted in the breakdown of African law and order, giving rise to violence. Globalisation has further added to the difficulty of establishing an ideal framework for defining and operationalizing the two notions at both the national and international levels. As a global community, the world should be controlled from a common holistic platform with an ideal global legal structure. The overall objective is to have a breed of political leaders who value life and provide human security and respect of human rights. Security and human rights compromise the most ambiguous and controversial concerns for the African community and world at large. Questionnaires and interviews, as well as secondary data sources, were employed to fulfill the research objectives. Hermeneutics and philosophical analytical methodologies serve as the foundation for my study. The findings of this study reveal a variety of evolving perspectives on governance, political leadership, and the rule of law in Africa. The most widely held, albeit controversial, belief is that African politics is incomplete without violence, rigging, and corruption. The rights to a decent standard of life, enough security, medical treatment, land, and peace have become political rights rather than common people’s rights, as this article demonstrates.